Emotional Deprivation in Children: Growth Faltering and Reversible Hypopituitarism - Rogol, Alan David (Frontiers in Endocrinology, 2020)
Emotional deprivation can lead to growth faltering of infants and children. The mechanism(s) involved differ in that for infants the major metabolic problem is inadequate energy intake for growth. In young children it is likely that the emotional deprivation causes a syndrome not only of growth faltering, but with bizarre behaviors, especially with regard to food: hoarding, gorging and vomiting, hyperphagia, drinking from the toilet, and eating from garbage pails.. Other disturbed behaviors include, poor sleep, night wanderings and pain agnosia. The pathophysiology appears to be reversible hypopituitarism, at least for the growth hormone and hypothalamic-pituitary- adrenal axes. The review begins with an historical perspective concerning stress, children and growth and then moves to the issue of hospitalism, where young infants failed to thrive (and died) due to inadequate stimulation and energy intake. Refeeding programs at the end of World Wars I and II noted that some children did not thrive despite an adequate energy intake. It appeared that in addition taking care of their emotional needs permitted super-physiologic (catch-up) growth. Next came the first notions from clinical investigation that hypopituitarism might be the mechanism of growth faltering. Studies that address this mechanism from a number of observational and clinical research studies are reviewed in depth to show that the hypopituitarism was relieved upon removal from the deprivational environment and occurred much too quickly to be due to adequate energy alone. These findings are then compared to those from malnourished children and adoptees from emerging countries, especially those from orphanages where their psychosocial needs were unmet despite adequate caloric intake. Together these various conditions define one aspect of the field of psychoneuroendocrinology.